Studi Komparasi Strategi Student Teams Achievement Division (STAD) dan Numbered Heads Together (NHT) Terhadap Hasil Belajar Matematika Siswa Kelas IV SDN 1 Siswodipuran Boyolali Tahun Ajaran 2015/2016 - Indriastuti, Nita (2016)
This study aims to determine (1) whether there is any significant difference in the effect of STAD and NHT towards learning outcomes maematika fourth grade students at SDN 1 Siswodipuran Boyolali, (2) a greater influence between STAD and NHT towards learning outcomes math grade IV SDN 1 Siswodipuran Boyolali Academic Year 2015/2016. This type of research is quantitative research experiment. Samples of this research is class IVA and IVB the number of 59 students. The method used in data collection are observation, interview, test and documentation. Data analysis technique using the t test.Based on the results of data analysis with significance level of 5% was obtained grades - ttabel ≤ thitung ≤ ttabel namely - ≤ 2.002 - 0.402 ≤ 2.002, with an average value of learning outcomes IVB class is greater than the average grade learning outcomes IVA is 71.34> 69.6. The conclusion of this research are (1) there is no significant difference STAD strategy and NHT influence on mathematics learning outcomes of fourth grade students at SDN 1 Siswodipuran Boyolali; (2) STAD and NHT strategy has the same effect in the learning of mathematics in particular the material units of time, although the average value generated through the implementation of both strategies have little difference. Keywords: comparison, learning outcomes, nht, stad